2019
DOI: 10.1175/jhm-d-18-0200.1
|View full text |Cite
|
Sign up to set email alerts
|

Representation of Precipitation Characteristics and Extremes in Regional Reanalyses and Satellite- and Gauge-Based Estimates over Western and Central Europe

Abstract: This paper evaluates several daily precipitation products over western and central Europe, identifies and documents their respective strengths and shortcomings, and relates these to uncertainties associated with each of the products. We analyze one gauge-based, three satellite-based, and two reanalysis-based products using high-density rain gauge observations as reference. First, we assess spatial patterns and frequency distributions using aggregated statistics. Then, we determine the skill of precipitation ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 61 publications
0
9
0
Order By: Relevance
“…These models are able to model data which are highly skewed and have heavy‐tailed distributions and, thus, are highly non‐Gaussian. There are also some other methods that were used in previous studies, including using the fractions skill score to assess the skill of a data set to represent the occurrence of extreme events in a reference data set (Lockhoff et al., 2019), and using the Taylor diagram to characterize the spatial structure of extreme events (Kharin et al., 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These models are able to model data which are highly skewed and have heavy‐tailed distributions and, thus, are highly non‐Gaussian. There are also some other methods that were used in previous studies, including using the fractions skill score to assess the skill of a data set to represent the occurrence of extreme events in a reference data set (Lockhoff et al., 2019), and using the Taylor diagram to characterize the spatial structure of extreme events (Kharin et al., 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Temperature and precipitation are two meteorological variables that are highly relevant to our lives. Previous studies have shown that precipitation extremes in gridded data products are often less reliable, compared to temperature extremes (Donat et al., 2014; Kharin et al., 2005; Lockhoff et al., 2019; Mannshardt‐Shamseldin et al., 2010; Zolina et al., 2004). Therefore, in this paper, we evaluate four gridded data products in terms of their performance on representing daily precipitation extremes over Germany.…”
Section: Introductionmentioning
confidence: 99%
“…From the daily gridded values, the country scale, annual air temperature, and precipitation estimates were calculated. Due to E-OBS uncertainties caused by gauge measurement errors, lack of wind corrections, and possible station relocations [38], the areal precipitation averages are considered to be underestimated [39,40]. To overcome the underestimation of the precipitation data available, a correction factor was applied to the annual precipitation totals derived from the E-OBS data.…”
Section: Datamentioning
confidence: 99%
“…Also, they showed that outputs of this model has not any advantage in compared with satellite or reanalysis data in Africa. Lockhoff et al (2019) evaluated some PCP outputs (data of a synoptic station, three satellite-based models, and two reanalysis-based models) in western and central Europe. Their results show that the quality of the datasets largely depends on the region, season, and PCP characteristic.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have so far been carried out around the world so far on global PCP datasets. They include studies performed in Central and Western Europe (Lockhoff et al 2019), China (An et al 2020;Bai et al 2020;Li et al 2018), Central Asia (Lu et al 2021), Australia and Africa (Awange et al 2019), India (Bhattacharyya et al 2022;Kolluru et al 2020), Thailand (Gunathilake et al 2021), Iraq and Eastern Africa (Salman et al 2019), Kenya, Uganda, and Tanzania (Garibay et al 2021). In addition, various research works in Iran have addressed global precipitation datasets for arid and semiarid regions (Darand and Khandu 2020;Eini et al 2019;Fallah et al 2020;Ghajarnia et al 2015;Hosseini-Moghari et al 2018;Izadi et al 2021;Keikhosravi-Kiany et al 2021;Nasseri et al 2021;Saemian et al 2021;Shayeghi et al 2020;Taghizadeh et al 2021).…”
Section: Introductionmentioning
confidence: 99%